Study of the influence of monetary incentives in conduction of experiments; Estudio de la influencia de los incentivos en la conducción de experimentos - Víctor Pe\~na Vargas; Rogelio Ladrón de Guevara Cortés; Alina Gomez Mejia; Jorge Enrique Velasco Diaz (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
The use of monetary incentives in experiments is a subject of intense debate in academic literature, since there is no consensus regarding its suitability as a tool to encourage the participants of an experiment. Several authors consider it essential, others, however, dismiss its use. This article studies the influence that monetary incentives may or may not produce on the results provided by the participants of an experiment. To this end, an experiment was conducted with 280 university students, which involved forecasting the future value of a financial index. The experiment was comprised of two phases and was applied to two groups of people. Group 1 was formed with 124 students, to whom a monetary incentive for their participation was offered. Group 2 consisted of 156 students, although considering the difference of not offering a monetary incentive, their participation being free and voluntary. This permitted the comparison of results of both groups with the aim of establishing the degree of influence of the monetary incentive. Likewise, taking into consideration that a financial forecast based on the present value was performed, the influence of the anchoring and adjustment heuristics was measured. Results were analyzed by means of the Mann-Whitney non-parametrical test and the Chi2 test. It can be concluded that the monetary incentive does not have an impact on the participants' responses, and the influence of the anchoring and adjustment heuristics in the forecasting of the financial index used in the study was confirmed.
Keywords: D9; G1; G4; G41; 330; Behavioral Finance; Financial Forecast; Anchoring and Adjustment Heuristics Judgment; Monetary Incentive